Time-series analysis through motor programming for sequence punches - Abdel-Aziz Habib, H. (World Journal of Sport Sciences, 2010)
The research problem is represented in the attempt to focus on the motor series of sequence punches due to their utmost importance to the Boxer`s ability to score more points during the boxing matches; through using the motor programming method of sequence punches (Straight Sequence Punches). The research aims to identify the phases of construction a motor program for Straight Sequence Punches through the time-series analysis of the motor sequence in this search. The search sample consisted of a single international player who performed a sequence of 360 repetitions punches distributed to six exercise sessions, The search implementation took 6 consecutive practice days, and daily practice lasted 65 minutes, and included 60 repetitions of the sequence punches over the practice days, the boxer was filmed 6 consecutive times) after every 60 repetition of the sequence punches.. The researcher used the descriptive method through using highspeed camera, frequency (250 frame / second) and the Kinematographic analysis. The most important research results indicated that the motor sequence which can be performed sequentially and in a time less than the reaction time is a programmed sequence because their performance does not depend on feedback, in accordance with the concept of the Motor Program. The time-series analysis of straight sequence punches proved that the length of time is the basis to judge the speed of programmable variable compared to another. Interference time has played the first role in construction the motor program, followed by reverse time, then punching time, and then total time for each punch.